Degradation of endocannabinoids in chronic migraine and medication overuse headache - L.M. Cupini (Neurobiology of Disease, 2008)
Chronic migraine (CM) is frequently associated with medication overuse headache (MOH). The endocannabinoid system plays a role in modulating pain including headache and is involved in the common neurobiological mechanism underlying drug addiction and reward system. Anandamide (AEA) and 2-arachidonoylglycerol are the most biologically active endocannabinoids, which bind to both central and peripheral cannabinoid receptors. The level of AEA in the extracellular space is controlled by cellular uptake via a specific AEA membrane transporter (AMT), followed by intracellular degradation by the enzyme AEA hydrolase (fatty acid amide hydrolase, FAAH). AMT and FAAH have also been characterized in human platelets.We assayed the activity of AMT and of FAAH in platelets isolated from four groups of subjects: MOH, CM without MOH, episodic migraine and controls. AMT and FAAH were significantly reduced in CM and MOH, compared to either controls or episodic migraine group. This latter finding was observed in both males and females with CM and MOH. Changes observed in the biochemical mechanisms degrading endogenous cannabinoids may reflect an adaptative behaviour induced by chronic headache and/or drug overuse.